The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.33448/rsd-v11i9.32024
|View full text |Cite
|
Sign up to set email alerts
|

Finding new meaning through music after a suicide attempt

Abstract: Listening to music can trigger unpleasant feelings or bring meaning to our lives, both from the cognitive and psychic perspectives. Thus, music can attribute meanings to our personal experiences and act as a regulator of emotions when living these experiences. Song lyrics can often influence behaviours while helping to work on processes of resilience, autonomy, empowerment, and psychosocial rehabilitation. This study aims to analyse the possibilities of music in the process of resignification of life through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In some cases, song lyrics and rhythms have impacted the behaviors of individuals and groups, positively or negatively, including suicidality and self-harm. Some research suggests that various musical genres such as rock, pop, country, blues, punk, and heavy metal, can influence suicidal ideation and behavior (Alves et al, 2022;Niederkrotenthaler et al, 2021;Stack & Gundlach, 1992). To illustrate, the findings from Stack & Gundlach's (1992), "multiple regression analysis of 49 metropolitan areas [in the United States] showed that the greater the airtime devoted to country music, the greater the white suicide rate" (p.211).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, song lyrics and rhythms have impacted the behaviors of individuals and groups, positively or negatively, including suicidality and self-harm. Some research suggests that various musical genres such as rock, pop, country, blues, punk, and heavy metal, can influence suicidal ideation and behavior (Alves et al, 2022;Niederkrotenthaler et al, 2021;Stack & Gundlach, 1992). To illustrate, the findings from Stack & Gundlach's (1992), "multiple regression analysis of 49 metropolitan areas [in the United States] showed that the greater the airtime devoted to country music, the greater the white suicide rate" (p.211).…”
Section: Introductionmentioning
confidence: 99%